Mitigation of nitrofuran residues in Scylla olivacea (Herbst,1796) through dietary Lacto-sacc supplementation - Md. Jahidul, Hasan; Md. Bodrul, Munir; Roslianah, Asdari; Md. Shoebul, Islam; Rabina A., Lima; Al-Amin, -; Md. Saiful, Islam; Rajib, Roy (Bioflux, 2025)
Nitrofuran metabolites, particularly semicarbazide (SEM), 1-aminohydantoin (AHD), 5-methylmorpholino-3-amino-2-oxazolidinone (AMOZ), and 3-amino-2-oxazolidinone (AOZ), pose significant risks in aquaculture due to their carcinogenic properties and strict zero-tolerance regulations. This study investigated the effectiveness of a probiotic mixture of Lactobacillus acidophilus and Saccharomyces cerevisiae (Lacto-sacc) in reducing nitrofuran residues in the range mud crab, Scylla olivacea (Herbst, 1796). Three diets were formulated: a control (0%) and treatments supplemented with Lacto-sacc at 1.0% and 1.5%. They were housed in breeding boxes inside earthen mangrove broodstock cages designed to simulate natural settings. The crabs were fed Lacto-sacc supplemented diets for 84 days before being tested for nitrofuran metabolites (SEM, AHD, AMOZ, and AOZ) by liquid chromatography-tandem mass spectrometry. Initial SEM concentratio ns in control crabs were 1.25±0.06 µg kg -1 , which increased to 1.42±0.04 µg kg -1 after the experimental period. In contrast, SEM levels declined significantly with probiotic supplementation: from 1.24±0.07 to 0.61±0.02 µg kg -1 in the 1.0% group, and 1.27±0.04 to 0.41±0.01 µg kg -1 in the 1.5% group (p < 0.05). Reductions in other nitrofuran derivatives, including AOZ and AMOZ, followed similar trends. Notably, SEM concentrations in the 1.5% treatment fell below the recommended permissible allowance (RPA) (0.5 µg kg -1 ) set by the European Food Safety Authority. These findings demonstrate that dietary supplementation with Lacto-sacc, particularly at 1.5%, can effectively mitigate nitrofuran metabolite accumulation in orange mud crabs. The use of probiotics offers a practical, eco-friendly approach to ensuring food safety, enhancing consumer confidence, and promoting sustainable aquaculture practices.